Pengujian Kinerja Keuangan terhadap Financial Distress pada Perusahaan Food and Beverage di BEI Tahun 2020-2023 - Erikawati, Civi; Muktiana, Nurul Aini Intan; Huda, Fathul (Borobudur Management Review, 2024)
This research aims to analyze the impact of financial ratios, namely Return on Assets (ROA), Debt to Equity Ratio (DER), Current Ratio (CR), and Total Asset Turnover (TATO), on financial distress in Food and Beverage companies listed on the Indonesia Stock Exchange (IDX). The sampling technique used in this research is purposive sampling, focusing on the food and beverage sector, with a sample of 30 companies over a period of 4 years from 2020 to 2023. Thus, the total data used in this research comprises 120 data points. The independent variables in this study are ROA, DER, CR, and TATO. The dependent variable is the condition of financial distress, expressed numerically. The research methodology employs the Zmijewski method to assess financial distress. The urgency of this research is to analyze the influence of financial performance on financial distress in food and beverage companies on the IDX in 2020-2023.. The data analysis method used in this research is multiple linear regression analysis, which helps in determining the influence of the independent variables (ROA, DER, CR, and TATO) on financial distress. The results of the t-test indicate that ROA significantly affects financial distress, whereas DER, CR, and TATO do not have a significant impact. Meanwhile, the F-test results show that the independent variables collectively have a significant influence on financial distress.